Muerte súbita - Donner, Richard.; Emmett, Randall.; Lerner, Avi.; Morse, David, 1953-; Mos Def (Cantante de rap); Rifkin, Arnold.; Thompson, John.; Van Wyck, Jim.; Wenk, Richard.; Willis, Bruce, 1955- (Warner Home Video, 2006)
Jack Mosley is a burnt-out detective who is assigned the unenviable task of transporting a fast-talking convict from jail, 16 blocks to the 100 Centre Street courthouse. However, as the two head off, Mosley learns that the man is supposed to testify against Mosley's colleagues, and the entire NYPD want the witness dead. Mosley must choose between loyalty to his colleagues and protecting the witness.